2021
DOI: 10.1002/lno.11887
|View full text |Cite
|
Sign up to set email alerts
|

Diatom frustules with different silica contents affect copepod grazing due to differences in the nanoscale mechanical properties

Abstract: The silica frustules of diatom are regarded as an important physical defense against predation. While the biogenic silica content of diatoms is a major factor controlling the ingestion rate of copepods, how it affects the three‐dimensional structure and the mechanical properties of the frustules, and consequently copepod grazing, has not been studied. In this study, the diatoms Thalassiosira weissflogii and Amphora coffeaeformis were grown under different light intensities to manipulate their cellular biogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…Thus, the sizethreshold for swallowing/crushing cells before ingestion may be around 10 μm, hence accounting for the difference in the degree of selectivity and handling times between small and large prey in our experiments. This could also, at least in part, explain the recent findings of Xu et al (2021) who reported that increased silica content in the diatom Amphora coffeaefornis had no defensive benefit, but rather the opposite, as copepods had higher ingestion rates on cells with increased silica content. The size of A. coeffeaefornis in their experiments was just $ 8 μm ESD (it is also elongated in shape, i.e., the actual width of the cell is < 8 μm), and in our experiments we clearly see a decrease in the efficiency of the defense with decreasing cell size.…”
Section: Discussionmentioning
confidence: 87%
“…Thus, the sizethreshold for swallowing/crushing cells before ingestion may be around 10 μm, hence accounting for the difference in the degree of selectivity and handling times between small and large prey in our experiments. This could also, at least in part, explain the recent findings of Xu et al (2021) who reported that increased silica content in the diatom Amphora coffeaefornis had no defensive benefit, but rather the opposite, as copepods had higher ingestion rates on cells with increased silica content. The size of A. coeffeaefornis in their experiments was just $ 8 μm ESD (it is also elongated in shape, i.e., the actual width of the cell is < 8 μm), and in our experiments we clearly see a decrease in the efficiency of the defense with decreasing cell size.…”
Section: Discussionmentioning
confidence: 87%
“…In fact, as already reported (Hamm et al, 2003;Friedrichs et al, 2013;Liu et al, 2016;Zhang et al, 2017;Xu et al, 2021), silicon deposition in the diatom cell wall is adopted as selective criterion by predators to choose suitable preys since higher silicification provides a stronger armour against predation, decreasing diatoms palatability.…”
Section: Introductionmentioning
confidence: 94%
“…Overall, this supports the possibility that MTB lived in hypoxic environments earlier in Earth history in the Archean ocean ( 17 , 56 ). Last, by forming intracellular silica globules, WYHC-5 cells accumulate as much as ~10.9% of the cell weight as silicon, which is comparable to the amounts of silica accumulated extracellularly by some silicifying eukaryotes such as the diatoms Thalassiosira weissflogii (9.6%) and Amphora coffeaeformis (18.0%) ( 57 ). As a result, before eukaryotes, these MTB forming intracellular silica may have contributed to the biogeochemical cycle of silicon since the middle Archea.…”
Section: Discussionmentioning
confidence: 94%